The Effect of Work Environment and Work Motivation on Employee Loyalty Dinas Perhubungan Kabupaten Tasikmalaya - Fazdi Syah Praja; Kusuma Agdhi Rahwana; Barin Barlian (Journal of Indonesian Management, 2023)
This research aims to find out the simultaneous and partial effect between the work environment and work motivation on employee loyalty Dinas Perhubungan Kabupaten Tasikmalaya. The research method used is a quantitative method with a survey approach. The population in this research is the employee in Dinas Perhubungan Kabupaten Tasikmalaya which amounts is 87 people and the sample is 37 respondents who is an employee of the secretariat, transportation sector, traffic sector, infrastructure facility sector, public communication information sector, informatics and coding sector and UPTD testing motorized vehicles, used purposive sampling technique. The data used is primary data. The analytical tool used in this study is multiple regression using SPSS 25. The results showed that simultaneously the work environment and work motivation has significantly affect on employee loyalty. Partially the work environment has a significant effect on employee loyalty. Partially the work motivation has a significant effect on employee loyalty.